Innovation for Educating on the Harm from Tobacco Smoking – the Smoke Trap Bottle - Thitiwattanakul, Uraiwan (Journal of Health Science of Thailand, 2019)
The objective of this study was to assess the outcomes of using an educational device, a smoke trap bottle, to raise awareness on the harm from tobacco smoking. The study samples were 84 grade 4 secondary school students from 2 schools in Nachaluai District, Ubonratchathani Province. It was conducted during the period from 16 December 2016 to 26 June 2017. The study tools were a smoke trap bottle to demonstrate the trapping of tobacco smoke, and a set of questionnaire. Students were educated on the harm of tobacco through the use of the bottle and the practical learning process comprising of presentation, group discussion, game play, demonstration and practice of 1 day duration. Pre-test and post-test data were collected one week before and one week after the intervention, respectively; and were compared by using descriptive and inferential statistics (paired t-test). It was found that after the learning exercise, the students had significantly higher knowledge and attitude scores (p<0.005) when compared to those before the program. Thus, the education program with the use of smoke trap bottle had successfully increased the awareness of students on the harm of tobacco.. Therefore, the findings from this study should be useful for health personnel and educational institutions to plan and implement programs to prevent new smokers among students with the use of the smoke trap bottle.